A low-cost NiSe2 derived from waste nickel foam as a high-performance anode for sodium ion batteries. (January 2022) - Yu, Lu; Shao, Lianyi; Wang, Shige; Guan, Jieduo; Shi, Xiaoyan; Cai, Junjie; Tarasenko, Nikolai; Sun, Zhipeng
Abstract: Nickel selenide has a splendid future to become a hot anode for sodium ion batteries owing to the high theoretical capacity and unique electrical conductivity. Nevertheless, exploring low cost and high-performance nickel selenide is still critical to further application. Herein, NiSe2 with micro-structured features has been synthesized through a low-cost and one-step selenidation approach using disused nickel foam as raw material. Eminent reversible capacity (515 mAh g −1 at 0.1 A g −1 ), superior rate capability (310 mAh g −1 at 10 A g −1 ), and excellent cycling stability (318 mAh g −1 after 800 cycles at 1 A g −1 ) are exhibited for NiSe2 prepared at 550 °C for 4 h. Importantly, the initial Coulombic efficiency is also impressive (96%). Furthermore, the electrochemical mechanism is sufficiently explored by means of ex situ X-ray diffraction (XRD) and transmission electron microscopy (TEM). Besides, employing Na3 V2 (PO4 )2 F3 @rGO as cathode and NiSe2 as anode has been assembled the sodium ion full battery, which delivers two high discharge plateaus of 1.86 and 2.72 V and reveals preeminent rate capacity and cycling stability. This work will come out with a new avenue for fostering the evolution of new metal selenide materials for energy storage and others. Graphical abstract: Image 1 Highlights: A facile and straightforward solid method is utilized to prepare NiSe2 from disused nickel foam. Micro-sized NiSe2 reveals excellent electrochemical performance. Sodium storage mechanism in NiSe2 is related to the reversible formation of Ni and Na2 Se.